2015
DOI: 10.1007/978-3-319-17121-0_90
|View full text |Cite
|
Sign up to set email alerts
|

JNK Inhibition Reduced Retinal Ganglion Cell Death after Ischemia/Reperfusion In Vivo and after Hypoxia In Vitro

Abstract: Mitogen-activated protein kinases (MAPKs) are key regulators that have been linked to cell survival and death. Among the main classes of MAPKs, c-jun N-terminal kinase (JNK) has been shown to mediate cell stress responses associated with apoptosis. In Vitro, hypoxia induced a significant increase in 661W cell death that paralleled increased activity of JNK and c-jun. 661W cells cultured in presence of the inhibitor of JNK (D-JNKi) were less sensitive to hypoxia-induced cell death. In vivo, elevation in intraoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…PDE6 inhibition partly restored cGMP concentration and this could improve the phototransduction cascade in hypoxic explants. Retinal hypoxia/ischemia affects most neuronal cells types (photoreceptors, bipolar and ganglion cells) but ganglion cells are especially vulnerable [58]. Under our experimental conditions, we corroborated that mild hypoxia induced retinal degeneration through the whole porcine retinas by increasing TUNEL-positive cells.…”
Section: Discussionsupporting
confidence: 83%
“…PDE6 inhibition partly restored cGMP concentration and this could improve the phototransduction cascade in hypoxic explants. Retinal hypoxia/ischemia affects most neuronal cells types (photoreceptors, bipolar and ganglion cells) but ganglion cells are especially vulnerable [58]. Under our experimental conditions, we corroborated that mild hypoxia induced retinal degeneration through the whole porcine retinas by increasing TUNEL-positive cells.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, previous studies have demonstrated that JNK may play a major role in various forms of neuronal death. In the rat retinal ischemia-reperfusion model, inhibition of JNK activation significantly decreased cell apoptosis in the GCL, the inner nuclear layer (INL), and the photoreceptor layer 53 . In mice, JNK signaling was activated after axonal injury of RGCs, which may be the major early pathway triggering RGC death after axonal injury, and may directly link axonal injury to the transcriptional activity that controls RGC death 54 .…”
Section: Discussionmentioning
confidence: 99%
“…To induce human RGC death in vitro, we used an H/R model, which involves ischemia and reoxygenation under glucose-deprived culture conditions, as reported previously [19]. So far, numerous transgenic animal and mammalian models have been established as in vivo experiments to elucidate the cell death mechanism and evaluate neuroprotective agents in the retina [20][21][22][23][24][25][26][27][28]. Using these animal models, the effects of some neuroprotective agents against RGC cell death have been investigated, including the pyruvate dehydrogenase kinase inhibitor [20], kynurenic acid [21], simvastatin [22], valproate [23], pasireotide [24], prothymosin alpha [25], and the Jun N-terminal kinase inhibitors [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…So far, numerous transgenic animal and mammalian models have been established as in vivo experiments to elucidate the cell death mechanism and evaluate neuroprotective agents in the retina [20][21][22][23][24][25][26][27][28]. Using these animal models, the effects of some neuroprotective agents against RGC cell death have been investigated, including the pyruvate dehydrogenase kinase inhibitor [20], kynurenic acid [21], simvastatin [22], valproate [23], pasireotide [24], prothymosin alpha [25], and the Jun N-terminal kinase inhibitors [26][27][28]. However, these animal studies significantly differ from the situation in which human RGCs are exposed to ischemia-reperfusion.…”
Section: Discussionmentioning
confidence: 99%